SATU SENYAWA STEROID DARI DAUN GEDI (Abelmoschus manihot L. Medik) ASAL SULAWESI UTARA - Mamahit, Lexy (Sam Ratulangi University, 2009)
This research was aimed to isolate and identify the structure of secondary metabolites from gedi leaf. Inorder to achieve this research aim, an extraction of the gedi leaf tissue with methanol solvent had beencarried out. These extract then was partitioned in several organic solvents such as n-hexane, chloroform,and ethyl acetate. Further, the resulted partition was fractionation and purifying undergoes an appropriatemethod like liquid and vacuum pressure chromatography and also determining the melting points. Todetermine the chemical structure of the isolate, a compilation of several spectroscopic methods, such asinfrared (IR), 1H and 13C nuclear magnetic resonance (NMR), and an advanced NMR techniques(HMQC, HMBC, and COSY). Results of this research shown that one major constituent was isolated fromthe leaf of gedi : b-ï€sitosterol.